Prenatal assistance: father's participation in healthy pregnancy (Research, Society and Development, 2021)
The father's participation is crucial for the routine and development of a healthy pregnancy, as both are concerned with developing activities that benefit the pregnancy. There are countless benefits associated with the father's involvement in pregnancy, which must be incorporated since his diagnosis. In this context, this study aimed to identify the benefits of the father's participation in prenatal consultations. This is an integrative literature review. This type of study was chosen because it allows the synthesis and analysis of the scientific knowledge already produced on the topic “PRENATAL CARE: participation of the father in healthy pregnancy”. The PubMed databases of the National Library of Medicine, VHL (Virtual Health Library) and CINAHL (Cumulative Index to Nursing and Allied Health Literature) were consulted. Of the 10 (ten) studies included in this review, six (60%) were in the English language and four (40%) in the Portuguese language. In relation to the year of publication, the articles presented variations, gaining prominence in 2017 (30%). Brazil was the country with the most studies included (40%), followed by the Netherlands (20%). The predominant level of evidence was composed mainly of cross-sectional studies (70%). The ten studies presented within the practices found, the numerous benefits of the partner's presence in the face of prenatal consultations, as well as greater gender equality, healthy child development, more confidence of the pregnant woman and paternal health care.